Positive contrast from cells labeled with iron oxide nanoparticles: Quantitation of imaging data. Issue 5 (17th January 2017) - Magnitsky, Sergey; Zhang, Jinjin; Idiyatullin, Djaudat; Mohan, Geetha; Garwood, Michael; Lane, Nancy E.; Majumdar, Sharmila
Abstract : Purpose: Conventional T2 ‐weighted MRI produces a hypointense signal from iron‐labeled cells, which renders quantification unfeasible. We tested a SWeep Imaging with Fourier Transformation (SWIFT) MRI pulse sequence to generate a quantifiable hyperintense signal from iron‐labeled cells. Methods: Mesenchymal stem cells (MSCs) were labeled with different concentrations of iron oxide particles and examined for cell viability, proliferation, and differentiation. The SWIFT sequence was optimized to detect and quantify the amount of iron in the muscle tissue after injection of iron oxide solution and iron‐labeled MSCs. Results: The incubation of MSCs with iron oxide and low concentration of poly‐L‐lysine mixture resulted in an internalization of up to 22 pg of iron per cell with no adverse effect on MSCs. Phantom experiments showed a dependence of SWIFT signal intensity on the excitation flip angle. The hyperintense signal from iron‐labeled cells or solutions was detected, and an amount of the iron oxide in the tissue was quantified with the variable flip angle method. Conclusions: The SWIFT sequence can produce a quantifiable hyperintense MRI signal from iron‐labeled cells. The graft of 18 x 10 6 cells was detectable for 19 days after injection and the amount of iron was quantifiable. The proposed protocol simplifies the detection and provides a means to quantify cell numbers. Magn Reson Med 78:1900–1910, 2017. © 2017 International Society for Magnetic Resonance in Medicine.